GAMBARAN FAKTOR RESIKO PADA PENDERITA HIPERTENSI DI WILAYAH PUSKESMAS ABANG I, KABUPATEN KARANGASEM - Wan Azren (DiscoverSys Inc., 2015)
From January to December in 2013, hypertension included in 10 most diseases in the Public Health Center Abang I, which ranks fifth in with 830 cases and 230 patient visits. No data about patient with risk factors of hypertension from Public Health Center Abang I. Risk factor for hypertension is needed to be obtained in order to prevent hypertension. This research covers only the risk factors of hypertension based on age, gender, Body Mass Index (BMI), family history, alcohol consumption and smoking habits.Â This research is using descriptive quantitative research study with cross-sectional approach is done once data collection. Collection of sample used is multistage sampling. The population in this study is the population diagnosed with hypertension in Public Health Center Abang I during period January â€“ December 2013.Â Sample used is 60 people. Respondents with age over 65 years old has the highest proportion (33.4%). Respondent who does not working have the highest proportion (41.7%) of hypertension. Among group with only obtain primary education has highest proportion (41.7%), with family history which has the highest proportion (63.3%). Respondents with obesity I have the highest proportion (56.7%). Males who are smoking has the highest proportion (88%). Alcohol consumer has the highest proportion of hypertension (72%).Researcher obtained a trend of increased blood pressure due to increase of age, female, low education level, do not working, family history of hypertension, obesity, smoking, and alcoholic consumer.